2015
DOI: 10.1007/s12011-015-0387-3
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Selenium Compounds on the Proliferation, Apoptosis, and Angiogenesis of a Canine Breast Cancer Cell Line

Abstract: We herein examined the effects of different doses, forms, and compatibilities of selenium on a canine mammary gland tumor cell line, CTM1211, and explored the related mechanisms. Three selenium compounds, sodium selenite (SSE), methylseleninic acid (MSA), and methylselenocysteine (MSC), were selected for these experiments, and cyclophosphamide (CTX) served as a positive control. In the cell viability assay, the cell viability of each group at 48/72 h decreased significantly compared with the control group (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
0
26
0
1
Order By: Relevance
“…The most appropriate concentration and duration of MSC to incubate with HAECs might be 200 mmol/L and 24 h. The apoptosis rate of HAECs increased obviously when co-incubated with EA1 400 mmol/L MSC may due to cytotoxicity of MSC at high concentration (17). Reported studies approved that the most two common existence forms of selenium, inorganic selenium (such as sodium selenite) and organic selenium (such as methylseleninic acid and Se-methylselenocysteine) may exert bioactive or cytotoxic effects in vitro strictly depend on compound, concentration and model used (14,18). We use MSC in our model because increasing studies supported that MSC has stronger bioactivity than other forms of selenium in vitro (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most appropriate concentration and duration of MSC to incubate with HAECs might be 200 mmol/L and 24 h. The apoptosis rate of HAECs increased obviously when co-incubated with EA1 400 mmol/L MSC may due to cytotoxicity of MSC at high concentration (17). Reported studies approved that the most two common existence forms of selenium, inorganic selenium (such as sodium selenite) and organic selenium (such as methylseleninic acid and Se-methylselenocysteine) may exert bioactive or cytotoxic effects in vitro strictly depend on compound, concentration and model used (14,18). We use MSC in our model because increasing studies supported that MSC has stronger bioactivity than other forms of selenium in vitro (19).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, cells were divided into 5 groups: negative control (NC) group, elaidic acid (EA) group (50 mmol/L), EA1 MSC group (50 mmol/L1 100 mmol/L, 50 mmol/L1 200 mmol/L, 50 mmol/L1 400 mmol/L). The concentrations of EA and MSC used in this study were according to previous study (14,15). Three thousand cells per well were seeded into 96-well plates and incubated for 24 h and 48 h with different reagents.…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17][18] Despite the complex and ambiguous mechanisms of action, organoselenium compounds are proposed to induce DNA damage, regulate the cell cycle, inhibit cellular growth, induce apoptosis and generate ROS. [15][16][17][18][19] Furthermore, it has been reported that patients with melanoma, breast cancer, and pancreatic cancer have exhibited decreased selenium levels in whole blood or serum compared to healthy controls. 20 In spite of the mentioned importance of selenium and organoselenium compounds, there is evidence showing contradictory antioxidant behaviors in selenium containing compounds, suggesting that these compounds must be examined individually for its antioxidant conduct.…”
Section: Selenium and Healthmentioning
confidence: 99%
“…On the other hand, selenium has proven to be an important supplement for the suppression of the side effects of chemotherapy (Schroeder et al 2004;Markovic et al 2011;Brodin et al 2015;Mut-Salud et al 2016). Also, selenium-containing compounds exert inhibition of migration of cancer cells (Zec et al 2012;Chen et al 2013;Liu et al 2015). Combining palladium and selenium in the same structure could provide a novel substance with benefits from the both elements.…”
Section: Introductionmentioning
confidence: 99%